COMMUNICATIVE METHODS OF TEACHING ENGLISH VOCABULARY AND GRAMMAR IN CONTEXT - Numonova, Mukharramkhon (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
This paper examines the applicability of communicative approach in teaching of English vocabulary and grammar in context. Stemming from the communicative approach to language teaching that focuses on interaction and meaningful use of language, the paper explores how vocabulary and grammar learning can be contextualized in meaningful context and usage. Scholars criticized the conventional method of language teaching which involves memorization and repetitiveness of grammatical exercises, instead, there is a call for integrating effective practice in which students use language in real communicative practices. The paper used classroom practices and teacher-student interactions to reveal methods for the teaching of vocabulary and grammar, including task-based learning, content-based instruction, and authentic materials. Furthermore, the psychological perspectives of languages learning are provided in order to explain how these communication approaches meet the cognitive and social concerns of learners. Research data is used to back up the assertion that integrating new vocabulary and grammar promotes the effective acquisition, recall and application of linguistic items, while increasing the motivation of second or foreign language learners. Lastly, the paper offers a range of recommendations for the teachers, who are willing to use communicative methods in their classroom, and emphasizes flexibility and individual focus on students as the most crucial aspects of the constantly developing field of foreign language learning.